Post-burn axillary contracture: A therapeutic challenge! - Durga Karki; Nikhil Mehta; Ravi Prakash Narayan (Indian Journal of Plastic Surgery)
Background: Axillary post-burn scar contracture is a challenging problem to the reconstructive surgeon owing to the wide range of abduction that should be achieved. The aim of this paper was to highlight the various options used in managing axillary contractures in our hospital. Materials and Methods: This is a retrospective hospital-based study of axillary contractures managed at Safdarjung Hospital (a tertiary care hospital) from 2009 to 2013.The study consisted of 44 patients from all age group and both sex included in it. Patients with a bilateral axillary contracture were excluded. Axillary contracture was released and resurfaced using split skin graft and/or with different types of flaps including the propeller flap, parascapular flap. All the reconstructed cases were followed-up for a period of 12 months. Assessment was done on the basis of functional and aesthetic outcome. Results: Forty-four patients consisting of 25 males and 19 females presented with axillary contractures that involved 44 axillae. The mean age of the study group was 17.1 years. Injuries involved the anterior axillary fold in 8 (18.18%), posterior fold in ten (22.72%), both folds and axillary fossa in 14 (31.81%) and both folds plus part of the chest wall and arm (sparing the axillary fossa) in 12 (27.27%) axillae. Surgical treatment included split-thickness skin graft in 15 (34.1%), local skin flaps in 4 (9.1%), Z-plasties in 4 (9.1%), parascapular flaps in 3 (6.82%), while propeller flaps in 12 (27.27%) and square flap were used in 6 (13.64%) patients. The percentage of improvement in abduction had a mean of 156°. The functional and aesthetic results were satisfactory. Conclusion: The choice of surgical procedure for reconstruction of post-burn axillary contractures can be made according to the pattern of scar contracture and the state of the surrounding skin. The choice of a flap should have priority over the skin graft because of the superior functional and aesthetic results of flaps.